Reflections on the link between labor movement and left in Argentina. The metallurgical case between 1916 and 1943 - Camarero, Hernán; Ceruso, Diego (Cuadernos de Historia, 2016)
The metallurgical union in Argentina has been addressed historiographically but usually the focus was on their performance in the second half of the twentieth century. But the history of the organization of metalworkers is longstanding and forms a rich and vast experience. That is why our goal is to focus the behavior of the union between 1916 and 1943 in Buenos Aires and its surroundings in many aspects: the characteristics of the work process, their union, their struggles and internal dynamics. Also we address the involvement of ideological tendencies of the labor movement (anarchists, socialists, sindicalistas and communists), trying to measure the influence of each and conceptualizing their policies and organizational practices.